A survey of phishing attacks: Their types, vectors and technical approaches - Chiew, Kang Leng; Yong, Kelvin Sheng Chek; Tan, Choon Lin (Elsevier Ltd, 2018)
Phishing was a threat in the cyber world a couple of decades ago and still is today. It has grown and evolved over the years as phishers are getting creative in planning and executing the attacks. Thus, there is a need for a review of the past and current phishing approaches. A systematic, comprehensive and easy-to-follow review of these approaches is presented here. The relevant mediums and vectors of these approaches are identified for each approach. The medium is the platform which the approaches reside and the vector is the means of propagation utilised by the phisher to deploy the attack. The paper focuses primarily on the detailed discussion of these approaches. The combination of these approaches that the phishers utilised in conducting their phishing attacks is also discussed. This review will give a better understanding of the characteristics of the existing phishing techniques which then acts as a stepping stone to the development of a holistic anti-phishing system. This review creates awareness of these phishing techniques and encourages the practice of phishing prevention among the readers. Furthermore, this review will gear the research direction through the types of phishing, while also allowing the identification of areas where the anti-phishing effort is lacking. This review will benefit not only the developers of anti-phishing techniques but the policy makers as well. © 2018 Elsevier Ltd